A binder-free bivalent manganese oxide cathode elective structure with high activity in aqueous zinc ion batteries - Ho, Van-Chuong; Oh, Si Hyoung; Mun, Junyoung (John Wiley & Sons Inc., 2022)
Manganese-based oxides are being actively studied as cathode materials for rechargeable aqueous zinc ion batteries (AZIBs) because of their high capacity, cost-effectiveness, safety, and eco-friendliness. Herein, we propose a binder-free electrode of bivalent manganese oxide with the chemical composition of Mn5O8 deposited on stainless steel as a cathode of AZIBs. Mn5O8 nanoparticles with a layered structure, which provide a facile pathway for Zn2+ ion transport and diffusion, were directly deposited on a three-dimensional stainless steel mesh via a hydrothermal method using different temperatures. The structures of the active materials in the cathode were characterized by X-ray diffraction, high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, and field-emission scanning electron microscopy. The Mn5O8 cathode materials exhibited a high specific capacity of 254.98 mAh g(-1), and simultaneously demonstrated satisfactory reversible charge/discharge and high rate performance. The Zn2+ insertion/extraction behaviors were studied in detail by cyclic voltammetry. In addition, factors that influence the electrochemical performance of the cathode, such as the phase structure and particle size of manganese dioxide, are discussed. Smaller and homogeneous Mn5O8 particles provide a large interface area and facilitate more zinc ions for diffusion, leading to improved ionic current and specific capacity.